Ethical Concerns of Direct-to-Consumer Genetic Tests - Farahani Fereshteh Shahrabi (TalTech Journal of European Studies, 2022)
The rapid development of technology is having an enormous effect on our lives. Emerging technological solutions offer new possibilities in various fields and on different levels, either for ordinary human beings or organisations and governments. However, the ethical implications of such technologies on our lives, our societies, are often not fully understood and require careful analysis. This article focuses on one type of such technologies, genetic tests available to the public, analysing the potential ethical concerns in these tests being directly provided to the consumers.